Proverbs Translation Techniques from English into Arabic among Jordanian University Students - HMAIDAN, MARVET ABED AHMAD (Journal of Ecohumanism, 2024)
Proverbs are essential component of everyday language, and they offer a fascinating insight into cultures. They are short sayings of public wisdom with cultural origin and figurative meanings, known by native speakers and used in specific situations. The reason behind the importance of translating proverbs precisely is that they are an effective and powerful instrument for the transmission of culture, social morality, manners, traditional wisdoms, historical incidents, and thoughts of people from one generation to another. The main difficulty in translating proverbs lies in their metaphorical nature, as they are culture-bound expressions and carry an implicit meaning that goes beyond the literal meaning. This study aims to investigate the translation techniques used by the students of translation at Jordanians universities in translating English proverbs into Arabic. The study is qualitative by nature, but a quantitative analysis was carried out to calculate the frequencies of the employed techniques. In this case study, forty students were engaged as participants using a purposive sampling method. They were given a translation test to recognize the employed techniques in translating 10 proverbs. The analysis revealed that the used techniques in order were using a proverb of similar meaning but different form, using a proverb of similar meaning and form, and translation by paraphrase came in the last position. The study is significant in raising the students’ awareness of the best techniques in translating proverbs for future translation works. The study has implications on translators to give emphasis on the language and cultural perspectives in translating culture-bound expressions to achieve successful communication between cultures.